Ascorbic acid stability and non-enzymatic browning in stored heat-treated sweetened and unsweetened kalamansi (citrus microcarpa, Bunge) juice - Tolentino, Erlinda B.
The physico-chemical attributes of fresh kalamansi juice related to ascorbic acid degradation and non-enzymatic browning were determined. The results showed an average pH val;ue of 2.35 ± 0.025 (S.D.), % titratable acidity of 6.99 ± 0.40 (S.D.), amino nitrogen content ranging from 26.51 to 33.02 mgs per 100 grams of juice, ascorbic acid concentration of 28.5 to 42.49 mg%, optical density at 420 nm of 0.104 ± 0.025 (S.D.), ranges of total reducing sugars of 0.535 to 1.356, fructose of 0.297 to 0.698, glucose of 2.38 to 0.658, and, sucrose of 0.292 to 0.573 gram per 100 milliliters of juice. The copper content ranged from 0.16 to 0.19 ppm and from 0.39 to 0.53 ppm, for iron. The effects of storage under refrigeration (10-15°C) and ambient (~30°C) temperatures on some attributes related to ascorbic acid degradation and non-enzymatic browning of heat-treated sweetened and unsweetened calamansi juice were investigated. Two phases and modes of ascorbic acid decompoition in the samples stored at ambient temperature were observed: a rapid phase (presumed to be aerobic) and a slower phase (anaerobic). The rapid phase covered the first 21 days of storage in the unsweetened juice and the first 10 days of storage in the sweetened juice. The earlier induction of the anaerobic phase in the sweetened juice is considered to have contributed to the higher ascorbic acid retained in it after 11 weeks of storage. Linear relationships between log percent ascorbic acid retention and storage time indicated that ascorbic acid degradation was a first order reaction at 10-15°C and during the aerobic and anaerobic phases at ambient, ~30°C,temperature. Furfural accumulation was higher in the unsweetened juice and at ambient temperature, wherein ascorbic acid losses incurred were greater. Storage under refrigeration temperature did not prevent significant ascorbic acid loss, sucrose hydrolysis (sweetened sample), furfural build-up, browning index changes and decrease in amino nitrogen concentration (sweetened sample). However, the changes were minimal compared to those incurred at ambient temperature. Like ascorbic acid decomposition, non-enzymatic browning was temperature dependent. After a brief lag period of less tha 7 days, the experimental samples held at ambient temperature exhibited increased absorbance at 420 nm with time. The rate of browning was faster in the sweetened juice, resulting in a markedly discolored product after 11 weeks of storage. The addition of commercial sucrose to bring up soluble solids concentration in kalamansi juice to 40° Brix generally conserved ascorbic acid but accelerated non-enzymatic browning during the heat treatment as well as during storage. The inherent kalamansi juice constituents apparently involved in its non-enzymatic browning are: amino acids, reducing sugars and ascorbic acid.